Lacosamide and sodium channel‐blocking antiepileptic drug cross‐titration against levetiracetam background therapy. (6th October 2016) - Baulac, M.; Byrnes, W.; Williams, P.; Borghs, S.; Webster, E.; De Backer, M.; Dedeken, P.
Abstract : Objective: To assess prospectively the effectiveness of lacosamide (LCM) added to levetiracetam (LEV) after down‐titration of a concomitant sodium channel blocker (SCB) among patients with focal epilepsy not adequately controlled on LEV and SCB. Methods: In this open‐label trial, LCM was initiated at 100 mg/day and up‐titrated to 200‐600 mg/day over 9 weeks; SCB down‐titration started when LCM dose reached 200 mg/day. Patients remained on stable LCM/LEV doses for 12 weeks' maintenance (21‐week treatment period). The primary outcome was retention rate on LCM. Results: Due to recruitment challenges, fewer than the planned 300 patients participated in the trial, resulting in the trial being underpowered. Overall, 120 patients (mean age 39.7 years) started and 93 completed the trial. The most frequently used SCBs were lamotrigine (39.2%), carbamazepine (30.8%) and oxcarbazepine (27.5%). Eighty‐four patients adhered to protocol and discontinued their SCB after cross‐titration, but there was insufficient evidence for 36 patients. Retention rate was 73.3% (88/120) for all patients and 83.3% (70/84) for those with evidence of SCB discontinuation. Seizure freedom for patients completing maintenance was 14.0% (13/93). Discontinuation due to adverse events (6.7%) and lack of efficacy (3.3%) occurred primarily during cross‐titration. Most frequently reported adverse events during treatment were dizziness (23.3%), headache (15.0%) and fatigue (8.3%). Conclusions: In patients with uncontrolled seizures on LEV/SCB, the LCM/LEV combination appeared to be effective and well tolerated. A cross‐titration schedule—flexible LCM up‐titration, concomitant SCB down‐titration and stable background LEV—could present a feasible and practical approach to initiating LCM while minimizing pharmacodynamic interactions with a SCB.